2016
DOI: 10.1515/ntrev-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study with dipole moment calculation of new electronic states of the molecule BF

Abstract: The potential energy curves for the 45 singlet, triplet, and quintet electronic states in the representation 2s+1 Λ (+/-) of the BF molecule have been investigated using the complete active space self-consistent field (CASSCF) method with multireference configuration interaction (MRCI). The internuclear distance R e , the harmonic frequency ω e , the static dipole moment μ, the rotational constants B e , and the electronic transition energy with respect to the ground state T e have been calculated for the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Table 4 shows the calculated electric dipole moments of the molecules in comparison with previous work. 61 The agreement between the calculated and experimental values is quite good. The experimental value for BF has a rather large uncertainty, because the experimental setup is difficult and it has been suggested that the experimental value is underestimated.…”
Section: Bonding Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…Table 4 shows the calculated electric dipole moments of the molecules in comparison with previous work. 61 The agreement between the calculated and experimental values is quite good. The experimental value for BF has a rather large uncertainty, because the experimental setup is difficult and it has been suggested that the experimental value is underestimated.…”
Section: Bonding Analysismentioning
confidence: 61%
“…The dipole moment of BF has been calculated before and the inverse polarity B→F has been discussed using VB and MO methods. 61 a , i , k The studies underline the particular role of the lone pair MO at beryllium, which yields a large atomic contribution to the dipole moment. This becomes obvious from the shape of the Laplacian distribution of BF in Fig.…”
Section: Bonding Analysismentioning
confidence: 96%